2016
DOI: 10.1371/journal.pone.0161654
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Antibiotic Treatment and Subsequent Childhood Type 1 Diabetes: A Nationwide Danish Cohort Study

Abstract: BackgroundStudies link antibiotic treatment and delivery by cesarean section with increased risk of chronic diseases through changes of the gut-microbiota. We aimed to evaluate the association of broad-spectrum antibiotic treatment during the first two years of life with subsequent onset of childhood type 1 diabetes and the potential effect-modification by mode of delivery.Materials and MethodsA Danish nationwide cohort study including all singletons born during 1997–2010. End of follow-up by December 2012. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 31 publications
(39 reference statements)
4
52
0
1
Order By: Relevance
“…For instance, delivery mode by cesarean section might predispose children to obesity [14]. Moreover, children who were treated with antibiotics early in life (which possibly affected their microbial composition) had increased risk of becoming overweight and suffering autoimmune diseases later on [15,16].…”
Section: Microbial Developmentmentioning
confidence: 99%
“…For instance, delivery mode by cesarean section might predispose children to obesity [14]. Moreover, children who were treated with antibiotics early in life (which possibly affected their microbial composition) had increased risk of becoming overweight and suffering autoimmune diseases later on [15,16].…”
Section: Microbial Developmentmentioning
confidence: 99%
“…A Danish study including 858 201 singletons born between 1997 and 2010 revealed that use of broad-spectrum antibiotics during the first 2 years of life was associated with an increased risk of T1D during later years of life. 82 It is also of note that this rate of antibiotic-associated risk for T1D was modified by mode of delivery, being higher in children delivered by Csection than in their vaginally delivered counterparts. 82 2.7 | Breast milk feeding, gut microbiome, and T1D…”
Section: Antibiotics Gut Microbiome and T1dmentioning
confidence: 99%
“…Surprisingly, this trend was not seen with previous exposure to either antiviral or antifungal drugs, suggesting that the increased risk of T1D was primarily a consequence of disrupted communities of gut bacteria. A Danish study including 858 201 singletons born between 1997 and 2010 revealed that use of broad‐spectrum antibiotics during the first 2 years of life was associated with an increased risk of T1D during later years of life . It is also of note that this rate of antibiotic‐associated risk for T1D was modified by mode of delivery, being higher in children delivered by C‐section than in their vaginally delivered counterparts …”
Section: The Gut Barriermentioning
confidence: 99%
“…Amarri and colleagues have previously found that gut bacteria and gut permeability as well as other immune markers were significantly altered in breast-fed infants (89). Other early influences have been demonstrated in a Danish study where the authors found that antibiotics used in early-life increased the incidence of type 1 diabetes in young children: however, this was also related to the mode of birth delivery, which has major effects on determining the composition of gut microbiota at the time of birth (91). …”
Section: Shaping the Immune System Via Alterations In Gut Bacteriamentioning
confidence: 99%